The Unique Edition of the XIX Century About Kazakhs-Researchers of Central Asia (Herald of Journalism, 2018)
For the modern educational process - training specialists for the publishing industry, - it is importantto know the features of the publications of reference industry publications, in the past. Russian pre-revolutionarypublications, for example, were printed only with the permission of censors. The purpose ofthe work was to reveal the facts of mentioning the names of Kazakh scientists - the first geographers andethnographers, in foreign publications. In order to implement the scientific project, the authors reviewedthe collections of rare antique publications in the libraries of near abroad. The practical significance ofthe study is the introduction of previously unknown written information on the contribution of Kazakh56 Вестник. Серия журналистики. №3 (49). 2018Уникaльное издaниеХІХ векa о кaзaхaх-исследовaтеляхЦентрaльнойАзииscientists of the 19th century to the study of the geopolitical situation around Central Asia. The methodologyof the project is based on dialectics and modern principles of interdisciplinary research, at theintersection of the history of elitist book publishing, geography, ethnology, sociology, regional studies,economics and management of publishing. The results of the study made it possible to generalize theinformation obtained and to identify the elite type of printed publications in Russia, to classify them asa special genre of book products designed to enhance the image of the Romanov dynasty: a rare editioncame out with the permission of the emperor, since the Russian monarch was the curator of the activitiesof the Russian Geographical Society. The authors of the article found in the antique curiosity informationabout two Valikhanovs: Shokan and Gazi, who were of aristocratic origin, young researchers of CentralAsia. The study of the contents of the book confirms its value; the public did not previously known certainfacts of the biography of Chingizids Kazakhs. The publication is equipped with a reference deviceand is a good scientific printed production of a sectoral nature. Since the identified rare book is kept inthe Red Book Fund of the Kurgan Regional Library, access to it by domestic researchers makes it possibleto assess the practical significance of the find.Key words: Russia, emperor, Kazakhs, chingizids, publishing house, printing house, history, Suvorin,Shokan Valikhanov, geography, science, book.
Keywords: Russia, emperor, Kazakhs, chingizids, publishing house, printing house, history, Suvorin, Shokan Valikhanov, geography, science, book.